Effects of Sucrose and Nonnutritive Sucking on Pain Behavior in Neonates and Infants undergoing Wound Dressing after Surgery: A Randomized Controlled Trial - Mandee, Sahatsa; Buachai, Kusuma; Aroonpruksakul, Naiyana; Tantemsapya, Niramol; Buasuk, Tarinee (European Journal of Pediatric Surgery, 2020)
Introduction Wound dressing, a procedure that pediatric patients are commonly exposed to postoperatively, can cause strong physiological and pain behavioral responses despite being brief. This study evaluated the effects of using 24% sucrose plus a pacifier versus a pacifier alone to reduce the pain response from dressing wounds in neonates and infants.Materials and Methods Thirty-two neonates and infants who underwent surgery and required postoperative wound dressing were randomized to a pacifier group (n = 16) and a 24% sucrose plus pacifier group (“sucrose group”; n = 16). Demographic data, crying time, and pain behaviors were recorded using a video recorder. The pain behaviors were assessed independently using the neonatal infant pain scale (NIPS) by three assessors, who were expert in pediatric pain assessment and blinded to the subject allocations.Results Participants in the sucrose group were older than those in the pacifier group (6.19 ± 2.95 vs. 3.88 ± 3.2 months). While there were no differences in the NIPS scores of the two groups at 30, 120, and 240 seconds, the incidence of moderate-to-severe pain was lower in the sucrose group than the pacifier group at 120 seconds (37.5 vs. 50%). The crying time was lower in the sucrose group, but without statistical significance.Conclusion The 24% sucrose plus pacifier was not superior to the pacifier alone in decreasing pain behavioral responses. Dressing wound pain produced a high-intensity pain behavioral response. A pain management strategy should be developed to lessen the postoperative procedural pain in pediatric patients.
Keywords: neonatal pain; infant pain; sucrose; nonnutritive sucking; wound dressing